Impact of low-calorie diet plans and structured strength training regimens on body recomposition: A four-month case report - Anu Sasidharan; Suja Gopalakrishnan; Sreelakshmi Mohandas (Indian Journal of Health Sciences and Biomedical Research KLEU, 2023)
A normal body weight can be maintained by balancing skeletal muscle mass (SMM) and body fat mass (BFM). InBody™ 270 is an easy-to-use bioelectrical impedance device when it comes to monitoring body parameters such as SMM and BFM. Such body parameters when kept in balance can reduce lifestyle diseases. This case report is an attempt to elucidate the impact of different diet plans and exercise regimens on changing (recomposition) the body composition parameters (SMM, BFM, etc.). One of the authors performed the experiments and recorded the observations. The blueprint for the diet included strategies such as low-calorie plans and intermittent fasting. The exercise regimen had different combinations of whole-body strength training four times a week. Almost eight kg of BFM was lost. The body weight had been brought to normalcy, and at the same time, SMM was preserved due to dietary interventions and exercises.